Roles of CcDFR and CcOMT9 in the cyanidin biosynthesis and development of Cordyceps cicadae - Zeng, Zixuan; Zou, Yu; Cai, Weiming; Lin, Fu-Cheng; Wang, Hongkai (Frontiers in Microbiology, 2024)
Cordyceps cicadae is a traditional Chinese medicinal fungus known for its rich production of bioactive substances, particularly cyanidin, an anthocyanin commonly found in plants with notable anti-inflammatory, anti-tumor, antiviral, and antibacterial properties. This study revealed two key genes, CcDFR and CcOMT9, affecting cyanidin biosynthesis in C. cicadae. The roles of these genes in cyanidin production, growth, and development were elucidated through gene knockout method, phenotypic analysis, transcriptomics, and metabolomics. CcDFR deletion led to reduced cyanidin-3-O-glucoside (C3G), suppressed expression of cyanidin biosynthesis genes, impaired synnemata formation, decreased polysaccharide, and adenosine content, and diminished chitinase activity, Meanwhile, the ΔCcOMT9 mutant exhibited an increase in C3G production, promoted expression of cyanidin biosynthesis genes, rising bioactive compounds, suppressed RNA methylation, and led to phenylalanine accumulation without no effect on fruiting body formation. We revealed a distinct anthocyanin biosynthesis pathway in C. cicadae and identified two genes with opposite function, laying the foundation for future genetic modification of cyanidinproducing strains using modern biological techniques. This will shorten the production period of this valuable compound, facilitating the industrial-scale production of cyanidin.